2020
DOI: 10.1111/jtxs.12579
|View full text |Cite
|
Sign up to set email alerts
|

Examination of the Peleg and Normand equation during relaxation of wheat: The effect of holding time

Abstract: In this study, we analyzed the effect of the duration of relaxation experiments on the parameters of the model proposed by Peleg and Normand. The relaxation experiments were conducted for individual intact wheat kernels in compression. Single kernels were initially loaded with a force of 20 N, then maintained at a constant deformation over time of 300 s. For the following time intervals 0–10, 0–20, 0–30, 0–40, 0–50, 0–60, 0–120, 0–180, 0–240, and 0–300 s coefficients k1, k2 and Y(t) were determined according t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 39 publications
0
0
0
Order By: Relevance
“…The reason is attributed to the role of tillage in providing optimal conditions for plant and root growth, in addition to the fact that the growing bushes were at a lower rate, and thus the competition between plants and bushes to absorb nutrients water decreased, and this is consistent with what was reflected. Regarding the weight of 1000 grains, these results agree with [15][16] [17].…”
Section: Mjassupporting
confidence: 83%
“…The reason is attributed to the role of tillage in providing optimal conditions for plant and root growth, in addition to the fact that the growing bushes were at a lower rate, and thus the competition between plants and bushes to absorb nutrients water decreased, and this is consistent with what was reflected. Regarding the weight of 1000 grains, these results agree with [15][16] [17].…”
Section: Mjassupporting
confidence: 83%
“…This enables plant roots to access water as required. According to [7] ; [14]. the study found that conventional tillage resulted in higher productivity and growth characteristics in the wheat crop compared to low or no tillage systems, specifically zero tillage.…”
Section: Introductionmentioning
confidence: 99%